The impact of public health shocks on fertility intentions: evidence from the COVID-19 pandemic in China - Guo, Yiting; Mou, Yuqi; Peng, Yan; Zhang, Chen (Frontiers in Public Health, 2025)
BackgroundChina's persistent fertility decline poses serious long-term demographic and socioeconomic challenges. The COVID-19 pandemic has introduced additional uncertainty, raising questions about how external shocks affect fertility intentions in real time.ObjectiveThis study examines the causal impact of localized COVID-19 shocks on fertility intentions in China, as measured by high-frequency digital search data that capture real-time behavioral shifts.MethodsWe construct a monthly city-level fertility index based on Baidu search volumes for pregnancy-related keywords across 222 cities (2019–2022). COVID-19 exposure is measured using sustained “high-risk” status over 14 consecutive days. A staggered difference-in-differences design is employed, with robustness checks including imputation-based estimators, event-study analysis, and heterogeneity analysis by city characteristics.ResultsCOVID-19 shocks led to a significant 5.4% decline (p < 0.01) in fertility-related search activity across Chinese prefecture-level cities. Event study confirmed persistent post-shock suppression, while placebo simulations confirmed the robustness of the identification strategy. Heterogeneity analysis revealed stronger declines in cities with higher GDP per capita (p < 0.01), greater urbanization (p < 0.01), and larger female population shares (p < 0.01), highlighting the amplifying role of local socioeconomic conditions.ConclusionFertility intentions respond sharply to pandemic-related uncertainty, especially under pressure from economic and institutional constraints. The findings underscore the fragility of reproductive intentions under uncertainty and highlight the importance of tailoring fertility policy to local socioeconomic environments.